Caracterização de lesões desportivas no basquetebol - Almeida Neto, Antônio Francisco De [UNESP] (2013)
INTRODUCTION: Basketball is characterized with high injury rate. In the literature it's not defined whether or not there are differences between the sexes. OBJECTIVE: Characterize and analyze the incidence of athletic injuries in basketball players, comparing the sexes. MATERIALS AND METHODS: Fifteen under-23 category athletes of each sex were interviewed with the reported morbidity inquire. RESULTS: The age of the female and male teams, in average, was 18 ± 0.65 and 18.20 ± 1.57 years respectively. The male team had more injuries than the female one (respectively 2.6 ± 1.45 against 1.2 ± 1.18, p < 0.05). The joint damage was the most common injury in the male team, representing 58.97%, and the second most common in the female team (33.33%). The lower limbs were the most common injured sites (80.95% in the female and 69.23% in the male). The most frequent injury mechanism in the male team was the landing (43.59%), and in the female was the vertical jump (28.57%). In both teams the most injuries occurred during the training (61.9% in the female and 71.8% in the male). The absence was necessary in 47.62% (female) and 56.41% (male). Great part of the athletes didn't received any treatment (61.9% and 51.28% in the female and male team respectively). The return to the activities was mostly symptomatic, in both female and male team (85.71% and 84.62% respectively). CONCLUSION: The incidence of injuries in basketball is higher in the lower limbs. The male team is more likely to suffer injuries, and the main injury mechanisms were different between male and female team.